The concept and features of staffing of the State Criminal Executive Service and probation bodies in Ukraine (Law and Safety, 2023)
The sphere of criminal penalties in our country has been undergoing reform for many years, and even today, in the context of Ukraine's opposition to the open full-scale military invasion of the russian federation, the work on transforming and improving the national penitentiary system has not stopped. The Ukrainian government, in cooperation with the international community, academics and civil society, has already taken a number of important steps to humanise the system. At the same time, some rather important problematic issues on this path have not yet received proper scientific and theoretical study or legislative regulation, in particular, the problem of staffing the State Criminal Executive Service of Ukraine and authorised probation bodies. The current Strategy for Reforming the Penitentiary System of Ukraine describes the problems of staffing in a rather superficial and fragmentary way, in fact, everything is reduced to its purpose and most important tasks. Obviously, this approach does not contribute to the improvement of the principles and mechanisms of this provision, nor to the efficiency and quality of the reform of the penitentiary system as a whole.In order to intensify research work in this area, the existing approaches to the definition of the concept of staffing have been considered, its main features and structural elements (components) have been identified, and the content of the most essential properties has been characterised. Attention has been paid to the connection and correlation between staffing and personnel policy, and the definition of the concept of staffing of the State Criminal Executive Service of Ukraine and authorized probation bodies has been formulated. Emphasis has been placed on the expediency of legislative consolidation of the definition of the concept of staffing of bodies and services of the penitentiary system of Ukraine, and on the fact that staffing has a complex internal structure and managerial nature. In this regard, attention has been paid to the role of administrative and legal regulation in organising and streamlining the relations and processes of staffing in the system of the State Criminal Executive Service of Ukraine and authorised probation bodies.
Keywords: staffing; staffing policy; system; penitentiary system; staffing of the State Criminal Executive Service and authorised probation bodies.